ANALISIS FAKTOR-FAKTOR YANG MENDORONG KINERJA DOSEN TETAP PADA FAKULTAS KOMUNIKASI DAN BISNIS UNIVERSITAS TELKOM - Andini Andini; Yahya Arwiyah; Astadi Pangarso (Business Management Journal, 2016)
Related to the performance of the homebase lecturers  at the Faculty of Communications and Business, Telkom University, in conduct the Tri Dharma Perguruan Tinggi (Three Pillars of Tertiary Education), research and community service feels lacking. That is why this research is intended to know the performance condition also to see the factors that encourage and the factors that are dominant towards the performance of fixed lecturers at the Faculty of Communications and Business in Telkom University. The method that is used  in this research is descriptive analysis with factor analysis technique. The type of this research is quantitative research. The respondants in this research are the fixed lecturers at the Faculty of Communications and Business in Telkom University. The research data is obtained by distributing questionnaires towards 70 respondants and literature review. Based on the descriptive analysis result, fixed lecturers performance in the "good" category is about 77%. Factor analysis results states that ability factor, organizational structure factor, background factor, and perception factor are the factors that encourage the performance of the fixed lecturers at the Faculty of Communications and Business in Telkom University. The ability factor which is representated by attitude, motivation, expertise, discipline, effectivity, and efficiency factors has the highest value % of variance that is about 34,837%. Organizational structure factor which is representated by resource, leadership, work experience, and work design factor has the value % of variance about 10,588%. Background factor which is representated by initiative and demography factor has the value % of variance about 8,533% while the perception factor has the value % of variance about 7,630%.Keyword:Performance, Factor Analysis, Faculty of Communications and Business in Telkom University, lecturer performance